Learning the subtle dance: The experience of therapists who deliver mentalisation‐based therapy for borderline personality disorder. Issue 2 (12th July 2021) - Gardner, Kathryn Jane; Wright, Karen M.; Elliott, Alison; Lamph, Gary; Graham, Simon; Parker, Lucy; Fonagy, Peter
Abstract: Objectives: This study aimed to understand therapists' lived experiences of delivering mentalisation‐based therapy (MBT), including their experiences of service user change. Method: One‐to‐one semi‐structured interviews or focus groups were conducted with 14 MBT therapists and analysed using interpretative phenomenological analysis (IPA). Results: Four superordinate themes were identified: (1) experiencing the challenges and complexities of being with service users during MBT; (2) being on a journey of discovery and change; (3) being an MBT therapist: a new way of working and developing a new therapeutic identity; and (4) being a therapist in the group: seeing it all come together. Conclusion: Our findings highlight the complexity, challenges and individualised experience of working therapeutically with service users with a diagnosis of BPD. The study provides a perspective of service use change that is enriched by idiosyncrasies within the therapeutic encounter. We conclude with a consideration of implications for MBT research and clinical practice.